Social franchising of community-based HIV counselling and testing services to increase HIV testing and linkage to care in Tshwane, South Africa: study protocol for a non-randomised implementation trial - Simukai Shamu; Charles Chasela; Jean Slabbert; Thato Farirai; Geoffrey Guloba; Nkhensani Nkhwashu (BMC, 2020)
Abstract Background Meeting the ambitious UN 90-90-90 HIV testing, treatment and viral load suppression targets requires innovative strategies and approaches in Sub-Saharan Africa. To date no known interventions have been tested with community health workers (counsellors) as social franchisees or owner-managed businesses in Community-based HIV counselling and testing (CBCT) work. The aim of this methods paper is to describe a Social franchise (SF) CBCT implementation trial to increase HIV testing and linkage to care for individuals at community levels in comparison with an existing CBCT programme methods. Methods/design This is a two arm non-randomised community implementation trial with a once off round of post-test follow-up per HIV positive participant to assess linkage to care in low income communities. The intervention arm is a social franchise CBCT in which unemployed, self-employed or employed community members are recruited, contracted and incentivised to test at least 100 people per month, identifying at least 5 HIV positive tests and linking to care at least 4 of them. Social franchisees receive approximately $3.20 per HIV test and $8 per client linked to care. In the control arm, full-time employed HIV counsellors conduct CBCT on a fixed monthly salary. Primary study outcomes are HIV testing uptake rate, HIV positivity, Linkage to care and treatment rate and average counsellors' remuneration cost. Data collection will be conducted using both paper-based and electronic data applications by CBCT or SF counsellors. Data analysis will compare proportions of HIV testing, positivity, linkage to HIV care and treatment rates and counsellors' cost in the two study arms. Discussion The study will provide important insight into whether the SF-delivered CBCT programme increases testing coverage and linkage to care as well as reducing CBCT cost per HIV test and per HIV positive person linked to care. Trial registration Pan African Clinical Trial Registry PACTR201809873079121. The trial was retrospectively registered on 11 September 2018.